PENINGKATAN PENGETAHUAN DAN PENURUNAN TINGKAT DEPRESI PASIEN PENYAKIT GINJAL KRONIK Â YANG MENJALANI TERAPI HEMODIALISA DENGAN TERAPI PSIKOEDUKASI - Waluyo, Agus; Mustikasari (JURNAL KEPERAWATAN BINA SEHAT, 2016)
The incidence of depression is often experienced by patients with chronic kidney disease (CKD) who must undergo regular hemodialysis therapy. Depression usually occurs early in patient wo undergo regular hemodialysis therapy. This research was conducted to determine the effect of therapies of psychoeducation on the level of knowledge and level of depression in patients with CKD who undergo regular hemodialysis therapy. The method used was quasi-experimental pre-post test without control group, sampling techniques was by purposive sampling, with a sample of 17 patients. Analysis of data using t test. The result showed that the mean of knowledge of the patients increased from 7,88 to 18,35 after psychoeducation therapy (statistically significant p = 0,000). And the mean of depression in patients decrease from 18,76 into 16,76 after psychoeducation therapy (statistically significant p = 0,000). Concluded that psychoeducation therapy increases the knowledge and decrease the depression of the respondents. Psychoeducation therapy is recommended for psychiatric nursing developed as a therapy that can be administered to patients with CKD who are depressed hemodialysis therapy.Keywords: psychoeducation therapy, the level of knowledge and level of depression.